Catalytic generation of alkoxy radicals from unfunctionalized alcohols - Tsui, Elaine (Chem Sci, 2020)
Alkoxy radicals have long been recognized as powerful synthetic intermediates with well-established reactivity patterns. Due to the high bond dissociation free energy of aliphatic alcohol O–H bonds, these radicals are difficult to access through direct homolysis, and conventional methods have instead relied on activation of O-functionalized precursors. Over the past decade, however, numerous catalytic methods for the direct generation of alkoxy radicals from simple alcohol starting materials have emerged and created opportunities for the development of new transformations. This minireview discusses recent advances in catalytic alkoxy radical generation, with particular emphasis on progress toward the direct activation of unfunctionalized alcohols enabled by transition metal and photoredox catalysis.